A call for comparative research: Consequences of a rising income inequality for state activities - Renate Neubäumer (Institute for the Study of Labor (IZA), 2011)
The aim of this discussion paper is not only to activate a debate over the interrelation between rising income inequality and economic policy measures but also to initiate comparative research in several European countries and North America. It discusses the consequences of a rising income inequality and its implications for state activities and economic policy. Using a simple model it becomes evident that an increasing income inequality leads to higher government spending, as a share of Gross Domestic Product, though the state does not take over more responsibilities. It also leads to a higher tax share though rates of taxation are not increased. This forces economic politicians to act. If they want to prevent an increase of these shares in order not to fall behind in the international competition, they must accept a rising public debt and/or must move away from socially accepted value judgments about social standards, the degree of redistribution by taxes and/or an adequate supply of public goods. This might result in disenchantment with politics.
urn:nbn:de:101:1-201104213140
Keywords: E6; 330; economic policy; income inequality; macroeconomic key figures; state activities; Einkommensverteilung; Staatsquote; Verteilungspolitik; Internationaler Wettbewerb; Wirtschaftspolitik; Vergleich; OECD-Staaten